Changes in Low-Income Countries’ Wages as a Result of China’s Trade Liberalization - Xiaolei, Zhang; Chen Yang (International Journal of Advances in Business and Management Research (IJABMR), 2024)
The fast expansion of China’s economy and the following liberalization of its commerce have had far-reaching consequences for the world’s LICs. Focusing on the implications on labor markets and income distribution, this research analyzes how China’s trade liberalization has affected salaries in LICs. This research intends to provide light on how China’s trade policies have affected wage dynamics and societal shifts by reviewing the relevant literature. China’s exports have increased as the country has liberalized its trade policies and opened up to international markets. Wages in LICs have been affected, both positively and negatively, by the flood of Chinese imports. Wages in businesses that rely heavily on human labor have been hit especially hard by cheap Chinese imports. Because of this, low-skilled employees in LICs face more competition and less bargaining leverage, both of which contribute to wage stagnation or decline. The rise of China’s exports, however, has opened up new doorways for economic development and increased employment in LICs. Increased demand from China has fueled employment growth and pay inflation in LICs’ comparative advantage sectors including natural resources and specialized manufacturing. Chinese investment in low- and middle-income countries (LICs) has boosted local economies by creating jobs and raising salaries in the manufacturing and infrastructure sectors. The overall effect of China’s trade liberalization on LICs’ salaries is nuanced and sector-specific. Economic diversification, trade patterns, and the structure of LIC economies all have a role in shaping the size and direction of these impacts